In vitro propagation and structural analysis of apple tree - Rodrigues, Michele de Medeiros (2006)
Effects of different concentrations of saccharose on multiplicative rates of in vitro sprouts and on anatomy of vegetative organs of young apple plants were tested. The micropropagation was obtained by direct organogenesis starting from stem apexes and internodal segments. Explants were removed from young plants, germinated in vitro at two months age. For the anatomical analysis of vegetative organs, plantlets developped in M&S medium after 30 days of culture were used. Results showed that the medium without sucrose caused death of the explant. The highest rate of shoots appeared using explants of stem apexes, and the size of the shoots in the concentrations 30, 45 and 60 g L-1 varied between 1 and 3 cm. The leaf presents structural alterations according to the medium sucrose concentration.